THE INFLUENCE OF SOCIAL MEDIA ON CONSUMER PURCHASING DECISIONS - Indah Sulistiani; Hadenan Towpek (Adisam Publisher, 2025)
This research examines the influence of social media on consumer purchase decisions, focusing on how platforms such as Instagram, Facebook and Twitter shape consumer behaviour and perceptions. Social media provides quick and broad access to product reviews, recommendations and direct interaction with brands, which further influences purchase decisions. The role of influencers and paid content on social media is also an important factor in shaping consumer preferences and loyalty. However, challenges arise in the form of subjective and sometimes misleading information, which can cloud the decision-making process. Therefore, an effective marketing strategy on social media should emphasise openness and honesty, while consumers should be more critical in filtering information.